2018
DOI: 10.1093/neuros/nyy589
|View full text |Cite|
|
Sign up to set email alerts
|

Obese Patients Benefit, but do not Fare as Well as Nonobese Patients, Following Lumbar Spondylolisthesis Surgery: An Analysis of the Quality Outcomes Database

Abstract: BACKGROUND Given recent differing findings following 2 randomized clinical trials on degenerative lumbar spondylolisthesis (DLS) surgery, there is a need to better define how subsets of patients fare following surgery. OBJECTIVE To investigate the impact of obesity on patient-reported outcomes (PROs) following DLS surgery. METHODS A total of 12 high-enrolling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…11 However, it is important to note that several independent observational studies have demonstrated the beneficial role of adding instrumented fusion for patients undergoing surgical intervention for degenerative spondylolisthesis. 1,3,8,9,17 Some notable associations with patient satisfaction previously identified but not found to be significant in our cohort are worth discussing here. A preoperative diagnosis of depression has been found to be associated with lower odds of satisfaction in previous studies, which was not found to be significantly associated in our cohort.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…11 However, it is important to note that several independent observational studies have demonstrated the beneficial role of adding instrumented fusion for patients undergoing surgical intervention for degenerative spondylolisthesis. 1,3,8,9,17 Some notable associations with patient satisfaction previously identified but not found to be significant in our cohort are worth discussing here. A preoperative diagnosis of depression has been found to be associated with lower odds of satisfaction in previous studies, which was not found to be significantly associated in our cohort.…”
Section: Discussionmentioning
confidence: 51%
“…Among these sites, 12 sites came together to initiate a focused project to assess the impact of fusion on PROs in patients undergoing surgery for grade I lumbar spondylolisthe-sis. [7][8][9][10]35 This focused group consisted of 1) sites with a study coordinator and 2) a centralized auditing mechanism to ensure data accuracy. To determine the diagnosis of grade I spondylolisthesis, surgeons at each of the participating sites evaluated preoperative standing or dynamic radiographs.…”
Section: Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Among these sites, the 12 highest-enrolling sites that were enrolling patients into the lumbar spine module came together to initiate a focused project to assess the impact of fusion on PROs in patients undergoing surgery for grade I lumbar spondylolisthesis. 1,8,9,10,26 In order to determine the diagnosis of grade I spondylolisthesis, surgeons at each of the participating sites evaluated preoperative standing or dynamic radiographs. 1,8,9,10,26 The primary outcome of in-terest for this study was Oswestry Disability Index (ODI).…”
Section: Cohortmentioning
confidence: 99%
“…Obesity has been linked to increased costs of medical care [8]. Although obese patients benefit from at least some back surgeries, they do not fare as well as nonobese patients [9]. Although obesity has been linked to back pain [10], no studies were found that directly link obesity to back surgery requirements.…”
Section: Introductionmentioning
confidence: 99%